2020
DOI: 10.1177/0969141320937725
|View full text |Cite
|
Sign up to set email alerts
|

Determination of methylmalonic acid, 2-methylcitric acid, and total homocysteine in dried blood spots by liquid chromatography–tandem mass spectrometry: A reliable follow-up method for propionylcarnitine-related disorders in newborn screening

Abstract: Objectives Determination of methylmalonic acid, 2-methylcitric acid, and total homocysteine in dried blood spots by liquid chromatography–tandem mass spectrometry has usually been used as a second-tier test to improve performance of newborn screening for propionylcarnitine-related disorders. However, factors that potentially affect its detection results have not been investigated, and we aimed to evaluate these influencing factors and explore their potential utility i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…If the parents choose to report carrier result and the infant identified as carrier, we can provide genetic counseling for them. The top genes such as PAH , SLC22A5 , ACADS and MUT were most frequently reported for carriers known to have high carrier frequency in reported study [ 46 ], which could verify the relative high incidence of associated inborn disorders [ 50 , 51 ]. Some high-frequency mutations of DUOX2, HBB , ATP7B gene in our study were not found in previous investigations.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…If the parents choose to report carrier result and the infant identified as carrier, we can provide genetic counseling for them. The top genes such as PAH , SLC22A5 , ACADS and MUT were most frequently reported for carriers known to have high carrier frequency in reported study [ 46 ], which could verify the relative high incidence of associated inborn disorders [ 50 , 51 ]. Some high-frequency mutations of DUOX2, HBB , ATP7B gene in our study were not found in previous investigations.…”
Section: Discussionmentioning
confidence: 93%
“…Using NBGS, 4 cases were diagnosed with MMA, PCD and WD that had been missed by C-NBS. It has been reported that the determination of MMA by MS/MS has been affected by several factors, and one case was missed due to the concentrations of C3 and C3/C0 decrease with age [ 46 , 47 ]. However, unlike metabolites, genetic screening was sufficiently accurate and specific for inborn disorders because it does not vary with age, season or maternal status.…”
Section: Discussionmentioning
confidence: 99%
“…DBS from a subset of true-positive (TP) and false-positive (FP) samples (Table S1) were blinded and processed in one analytic batch. For each DBS, a single 1/8-inch diameter circle was punched into a 96-deepwell plate, mixed with 100 μL of a DBS extraction solution containing internal standards (prepared as 90 mL methanol, 10 mL water, 20 μL formic acid, 40 μL methylmalonic acid-D 3 [1 mg/mL], 40 μL each of NSK-B-1 and NSK-B-G1, 50 μL of MSK-A2 amino acids mix, 8 μL ornithine 13 C 5 [5 mg/mL], 2 μL citrulline 13 C 5 [5 mg/mL], 2 μL dimethylglycine D 6 [1 mg/mL], 10 μL uridine 13 C 5 [1 mg/mL], 40 μL orotic acid D 2 [6 mM]) and vortexed for 15 min. Following centrifugation at 1800Âg for 30 sec, supernatants (80 μL) were transferred to a new 96-deepwell plate and evaporated under nitrogen to dryness, and then reconstituted with 100 μL of a diluent solution (80% water, 20% methanol, 0.1% formic acid v/v/ v).…”
Section: Compound Verification and Blinded Validation Using Targeted ...mentioning
confidence: 99%
“…7,8 In contrast to first-tier screening using direct injection analysis, second-tier tests often use liquid chromatography-tandem mass spectrometry (LC-MS/MS) to increase specificity by distinguishing isomeric compounds [9][10][11][12] and evaluating additional disease-related metabolites. 3,13 False-positive cases can also be reduced using postanalytic tools applied to first-tier screening data with the Collaborative Laboratory Integrated Reports (CLIR), [14][15][16] and more recently using machine learningbased methodologies. [17][18][19][20] However, the improvement in screening performance with these approaches varies widely among disorders on the Recommended Uniform Screening Panel (RUSP), suggesting that identification and clinical validation of additional markers could further improve screening performance.…”
Section: Introductionmentioning
confidence: 99%
“…14 Some NS programs have further implemented the addition of measuring methylmalonic acid and/or 2-methylcitrate as secondary markers. [15][16][17][18] In addition to the biochemical changes, patients with MMA have a pleiotropic clinical phenotype characterized by heterogeneous multisystemic disease manifestations including, but not limited to, recurrent metabolic instability, propensity to develop encephalopathy with hyperammonemia, failure to thrive, feeding intolerance, metabolic strokes of the basal ganglia, developmental delays, hypotonia, optic nerve atrophy, pancreatitis, osteopenia, cardiomyopathy, chronic kidney disease, poor feeding, and overall, an increased risk for early death, especially those with mut 0 MMA. [2][3][4][19][20][21][22] These clinical phenotypes are heterogeneous and can vary greatly between affected individuals.…”
Section: Introductionmentioning
confidence: 99%